2003
DOI: 10.1203/01.pdr.0000081300.49749.87
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intratracheal Recombinant Human Clara Cell Protein in a Newborn Piglet Model of Acute Lung Injury

Abstract: Despite the widespread use of exogenous surfactant, acute and chronic lung injury continues to be a major cause of morbidity in preterm infants. CC10 is a protein produced by Clara cells that inhibits phospholipase A 2 and has anti-inflammatory and antifibrotic properties. We studied whether intratracheal (IT) recombinant human Clara cell protein (rhCC10) could safely minimize lung injury in a newborn piglet model of acute lung injury. Twenty-nine newborn piglets were given Survanta and then ventilated for 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
6
35
0
Order By: Relevance
“…rhCC10 (5 mg/kg diluted to a total volume of 2 mL/kg with normal saline) was instilled with the piglets in a 30-degree Trendelenberg (head-down) position in two divided doses in the left and right lateral decubitus positions. The rhCC10 was produced in Escherichia coli bacteria according to published methods (Claragen, Inc., Germantown, MD) (15). The protein for the study was a Ͼ98% pure solution of the human CC10 homodimer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…rhCC10 (5 mg/kg diluted to a total volume of 2 mL/kg with normal saline) was instilled with the piglets in a 30-degree Trendelenberg (head-down) position in two divided doses in the left and right lateral decubitus positions. The rhCC10 was produced in Escherichia coli bacteria according to published methods (Claragen, Inc., Germantown, MD) (15). The protein for the study was a Ͼ98% pure solution of the human CC10 homodimer.…”
Section: Methodsmentioning
confidence: 99%
“…The protein for the study was a Ͼ98% pure solution of the human CC10 homodimer. The biologic activity of each batch was compared using a previously published secretory PLA 2 inhibition assay for rhCC10 (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic mice deficient in CCSP have been demonstrated to have exaggerated pulmonary inflammatory responses to hyperoxia and higher mortality rates [59]. Intra-tracheal treatment with exogenous CCSP tended to improve gas exchange and lung compliance in newborn piglets exposed to a hyperoxic injury [60]. A study in a premature lamb model found that treatment with synthetic recombinant human Clara cell secretory protein (rhCC10), increased surfactant protein and VEGF levels [61].…”
Section: Clara Cell Secretory Proteinmentioning
confidence: 99%